A thermoresponsive and magnetic colloid for 3D cell expansion and reconfiguration - Saeed, Aram Omer; Francini, Nora; White, Lisa; Dixon, James E.; Gould, Toby W.A.; Rashidi, Hassan; Cheikh Al Ghanami, Racha; Hruschka, Veronika; Redl, Heinz; Saunders, Brian R; Alexander, Cameron; Shakesheff, Kevin (Wiley, 2015)
A dual thermoresponsive and magnetic colloidal gel matrix is described for enhanced stem-cell culture. The combined properties of the material allow enzyme-free passaging and expansion of mesenchymal stem cells, as well as isolation of cells postculture by the simple process of lowering the temperature and applying an external magnetic field. The colloidal gel can be reconfigured with thermal and magnetic stimuli to allow patterning of cells in discrete zones and to control movement of cells within the porous matrix during culture.